A treacherous case of primary non-Hodgkin lymphoma of the bone: appearances can be deceptive. Issue 3 (August 2015) - Anyfanti, Panagiota; Gouridou, Eugenia; Tsinaridis, Apostolos; Bekiaropoulos, Dimitrios; Argyropoulos, Eleftherios; Sousos, Nikolaos; Petrou, Ioannis; Papathanasiou, Maria; Morichovitou, Anthi; Damianidis, Georgios; Bakatselos, Spyros
Introduction: Primary lymphoma of the bone constitutes an extremely rare but distinctive clinical entity, accounting for approximately 3% of all primary bone malignancies and less than 1% of all non-Hodgkin lymphomas. Case presentation: We report a rare case of a male patient with an atypical clinical presentation of non-Hodgkin primary lymphoma of the bone, initially misdiagnosed as ankylosing spondylitis. To our knowledge, this is the first case in the literature in which magnetic resonance imaging was contra-indicated. The atypical radiological imaging of the tumor, despite its aggressiveness, rendered the diagnostic approach a challenging but strenuous process. Conclusion: Plain radiographs and even computerized tomography images of primary lymphoma of the bone may appear as normal, but other imaging modalities should be used including radionuclide scans, especially when imaging techniques of greater accuracy such as magnetic resonance imaging are contraindicated. A patient-centred approach with emphasis on the main symptoms is the key to the diagnostic challenge of revealing the extremely unusual cases of primary lymphoma of the bone.